The Empirical Failure of the Expectations Hypothesis of the Term Structure of Bond Yields - Sarno, Lucio; Thornton, Daniel L.; Valente, Giorgio (Journal of Financial and Quantitative Analysis, 2007)
This paper tests the expectations hypothesis (EH) using U.S. monthly data for bond yields spanning the 1952–2003 sample period and ranging in maturity from one month to 10 years. We apply the Lagrange multiplier test developed by Bekaert and Hodrick (2001) and extend it to increase the test power by introducing economic variables as conditioning information and by using more than two bond yields in the model and testing the EH jointly on more than one pair of yields. While the conventional bivariate procedure provides mixed results, the more powerful testing procedures suggest rejection of the EH throughout the maturity spectrum examined.